The Enigma of Progressively Partial Endoreplication: New Insights Provided by Flow Cytometry and Next-Generation Sequencing - Hřibová, Eva; Holušová, Kateřina; Trávníček, Pavel; Petrovská, Beáta; Ponert, Jan; Šimková, Hana; Kubátová, Barbora; Jersáková, Jana; Čurn, Vladislav; Suda, Jan; Doležel, Jaroslav; Vrána, Jan (Genome biology and evolution, 2016)
In many plant species, somatic cell differentiation is accompanied by endoreduplication, a process during which cells undergo one or more rounds of DNA replication cycles in the absence of mitosis, resulting in nuclei with multiples of 2C DNA amounts (4C, 8C, 16C, etc.). In some orchids, a disproportionate increase in nuclear DNA contents has been observed, where successive endoreduplication cycles result in DNA amounts 2C + P, 2C + 3P, 2C + 7P, etc., where P is the DNA content of the replicated part of the 2C nuclear genome. This unique phenomenon was termed "progressively partial endoreplication" (PPE). We investigated processes behind the PPE in Ludisia discolor using flow cytometry (FCM) and Illumina sequencing. In particular, we wanted to determine whether chromatin elimination or incomplete genome duplication was involved, and to identify types of DNA sequences that were affected. Cell cycle analysis of root tip cell nuclei pulse-labeled with EdU revealed two cell cycles, one ending above the population of nuclei with 2C + P content, and the other with a typical "horseshoe" pattern of S-phase nuclei ranging from 2C to 4C DNA contents. The process leading to nuclei with 2C + P amounts therefore involves incomplete genome replication. Subsequent Illumina sequencing of flow-sorted 2C and 2C + P nuclei showed that all types of repetitive DNA sequences were affected during PPE; a complete elimination of any specific type of repetitive DNA was not observed. We hypothesize that PPE is part of a highly controlled transition mechanism from proliferation phase to differentiation phase of plant tissue development.
Keywords: Endoreduplication; Orchidaceae; průtoková cytometrie; listy rostlin; Genome, Plant; High-Throughput Nucleotide Sequencing; polyploidie; Polyploidy; Cell Nucleus; replikace DNA; Flow Cytometry; Plant Leaves; Mitosis; mitóza; buněčné jádro; vysoce účinné nukleotidové sekvenování; endoreduplikace; DNA Replication; genom rostlinný